1994
DOI: 10.2307/4002843
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Population Dynamics of Beaked Sedge following Cattle Grazing

Abstract: We studied the effect of cattle grazing on shoot density and flux in 4 southwest Montana beaked sedge (Carex rostrato ex With.) stands for 2 years. Forty plots were protected and 40 plots were grazed by cattle in June and September of 1989 and 1990. The effect of grazing vs. no grazing on mean shoot density and emergence varied over time (treatment by time interactionP Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
8
1
1
Order By: Relevance
“…Although some tall montane sedges are relatively unaffected by grazing (Allen and Marlow 1994;McIlroy and Allen-Diaz 2012), our findings better align with results obtained by Clary (1995) and Sørensen et al (2009) who found high elevation and/or high latitude sedges to demonstrate more grazing effects than other vegetation. Stohlgren et al (1989), also working in Sequoia and using experimental clipping, determined that assemblages dominated in part by sedge were more affected than assemblages dominated in part by reed grass.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although some tall montane sedges are relatively unaffected by grazing (Allen and Marlow 1994;McIlroy and Allen-Diaz 2012), our findings better align with results obtained by Clary (1995) and Sørensen et al (2009) who found high elevation and/or high latitude sedges to demonstrate more grazing effects than other vegetation. Stohlgren et al (1989), also working in Sequoia and using experimental clipping, determined that assemblages dominated in part by sedge were more affected than assemblages dominated in part by reed grass.…”
Section: Discussionsupporting
confidence: 82%
“…Reed grass forms a dense root mat (Botti and Sydoriak 2001), which, in combination with a shoot density six times greater than sedge, should confer some protection from trampling via higher shear strength (Morrocco and Ballantyne 2008;Monz et al 2010). The greater effects of grazing on sedge relative to reed grass in our study were likely also driven in part by soil moisture (Jensen 1985;Marlow et al 1987;Allen and Marlow 1994), which is two to fourteen times greater in sedge than in reed grass in the Sierra (Neuman 1996; Holmquist and Schmidt-Gengenbach unpublished). Higher soil moisture and silt content may have contributed to the observed lower soil strength in sedge, which, coupled with a morphology that may be more easily penetrated, probably influences the observed patterns of hoof punching: conservatively twice as deep in sedge as in reed grass (Neuman 1996).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Limitations of livestock exclosures include their small size (relative to the larger watershed which influences runoff and sediment yield), haphazard placement, and variable or unknown site histories in terms of livestock activity, which can lead to inconsistent results (Sarr, 2002). Another limitation of many riparian exclosure studies is that the data are from sites on the same stream (Kauffman et al, 1983;Schultz and Leininger, 1990;Allen and Marlow, 1994;Green and Kauffman, 1995;Case and Kauffman, 1997;Dobkin et al, 1998;Clary, 1999;Brookshire et al, 2002) or from adjacent watersheds (Leege et al, 1981), leading to small sample sizes, questions of pseudoreplication, and an inability to extrapolate results to other areas.…”
Section: Discussionmentioning
confidence: 99%